A GC-MS/Single-Cell Method to Evaluate Membrane Transporter Substrate Specificity and Signaling - Fairweather, Stephen J.; Okada, Shoko; Gauthier-Coles, Gregory; Javed, Kiran; Bröer, Angelika; Bröer, Stefan (Frontiers in Molecular Biosciences, 2021)
Amino acid transporters play a vital role in metabolism and nutrient signalling pathways. Typically, transport activity is investigated using single substrates and competing amounts of other amino acids. We used GC-MS and LC-MS for metabolic screening of Xenopus laevis oocytes expressing various human amino acid transporters incubated in complex media to establish their comprehensive substrate profiles. For most transporters, amino acid selectivity matched reported substrate profiles. However, we could not detect substantial accumulation of cationic amino acids by SNAT4 and ATB0,+ in contrast to previous reports. In addition, comparative substrate profiles of two related sodium neutral amino acid transporters known as SNAT1 and SNAT2, revealed the latter as a significant leucine accumulator. As a consequence, SNAT2, but not SNAT1, was shown to be an effective activator of the eukaryotic cellular growth regulator mTORC1. We propose, that metabolomic profiling of membrane transporters in Xenopus laevis oocytes can be used to test their substrate specificity and role in intracellular signalling pathways.